Synthesis of mesoporous materials as nano-carriers for an antimalarial drug. Issue 6 (21st January 2016) - Amolegbe, Saliu Alao; Ohmagari, Hitomi; Wakata, Kosuke; Takehira, Hiroshi; Ohtani, Ryo; Nakamura, Masaaki; Yu, Chengzhong; Hayami, Shinya
Abstract : An antimalarial drug artesunate (ATS) was encapsulated in both functionalized MCM-41 and ordinary MCM-41 with an excellent loading capacity and sustained release behavior for possible biomedical applications. Abstract : An antimalarial drug artesunate (ATS) was encapsulated in both functionalized MCM-41 and ordinary MCM-41 with an excellent loading capacity and sustained release behavior for possible biomedical applications.